2023
DOI: 10.1038/s41598-023-31766-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optimal gestational weight gain for twin pregnancy in Southwest China: a retrospective study

Abstract: There is a lack of data on gestational weight gain (GWG) in twin pregnancies. We divided all the participants into two subgroups: the optimal outcome subgroup and the adverse outcome subgroup. They were also stratified according to prepregnancy body mass index (BMI): underweight (< 18.5 kg/m2), normal weight (18.5–23.9 kg/m2), overweight (24–27.9 kg/m2), and obese (≥ 28 kg/m2). We used 2 steps to confirm the optimal range of GWG. The first step was proposing the optimal range of GWG using a statistical-base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, chronic hypertension during twin pregnancies have been shown to increase the risk of GDM [ 22 , 23 ]. Previous studies have shown that gestational weight gain during twin pregnancies in China ranges from 15 to 21 kg [ 20 , 21 ]. Excessive gestational weight gain has also been identified as a risk factor for hypertensive complications during pregnancy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, chronic hypertension during twin pregnancies have been shown to increase the risk of GDM [ 22 , 23 ]. Previous studies have shown that gestational weight gain during twin pregnancies in China ranges from 15 to 21 kg [ 20 , 21 ]. Excessive gestational weight gain has also been identified as a risk factor for hypertensive complications during pregnancy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following adverse maternal and neonatal outcomes were reported in our study: Pre-pregnancy BMI [ 19 ]: Underweight, BMI < 18.5; normal weight, 18.5 ≤ BMI < 24; overweight, 24 ≤ BMI < 28; obesity, BMI ≥ 28. Excessive gestational weight gain [ 20 , 21 ]: Total weight gain (TWG) or gestational gain BMI (GWGR) exceeded the established standards: underweight and normal weight, TWG ≥ 21 kg or GWGR ≥ 0.58; overweight, TWG ≥ 20 kg or GWGR ≥ 0.55; obesity, TWG ≥ 18 kg or GWGR ≥ 0.50. Preterm birth: before 34 or 37 complete weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation